Pengaruh Strategi Ekspositori Terhadap Hasil Belajar Baca Tulis Al-Qur’an (BTQ) Siswa Kelas Lima SD Negeri 4 Puding Besar - Velyani, Melda; Hapsoh, Siti (LENTERNAL: Learning and Teaching Journal, 2023)
The focus of this research concerns the influence of expository strategy learning on the results of reading and writing the Al-Qur'an (BTQ) of fifth grade students at SD Negeri 4 Puding Besar. The purpose of this research is to determine the effect of expository strategy learning on the results of reading and writing the Al-Qur'an (BTQ) of fifth grade students at SD Negeri 4 Puding Besar. This type of research is quantitative research, using a simple linear regression method. The population of this research was all fifth grade students at SD Negeri 4 Puding Besar. And the total sample for this study was 32. The data collection technique for this research uses a questionnaire technique. The research instrument technique uses validity tests and data reliability tests. The results of this research show that in the Expository Strategy Learning variable (X) there were 32 students who filled out the questionnaire. Obtained results for Mean 51.53, Median 52.50, Mode 40.00, Standard Deviation 12.750, Variance 162.580, Range 47.00, Minimum 29.00, Maximum 76.00, Summary 1649.00. Meanwhile, for the variable Al-Qur'an Reading and Writing Results (BTQ) (Y), there were 32 students who filled out the questionnaire. Obtained results for Mean 58.71, Median 59.00, Mode 52.50, Standard Deviation 11.562, Variance 133.693, Range 42.00, Minimum 38.00, Maximum 80.00, Sum 1879.00. So it can be said that the influence of the Expository Strategy Learning variable (X) on the Al-Qur'an Reading and Writing (BTQ) Result variable (Y) is 48.8% while the remaining 51.2% is influenced by other factors. Based on the results of the Fisher test, the value of Sig0.00<0.05 means that Ha is accepted so that there is a significant influence between Expository Strategy Learning on Al-Qur'an Reading and Writing (BTQ) Results.